Teori Konsumsi, Produksi dan Distribusi dalam Pandangan Ekonomi Syariah - Nur Fadilah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
The most fundamental reason why economics arises and is needed by humans, is because human needs are unlimited while the resources to meet those needs are limited. To overcome this, there are two main things that become the orientation of economics, namely choosing and creating. Choosing related to consumption and distribution, and creating related to production. Thus, the three activities (production, distribution, and consumption) have a very important role in solving economic problems. Islam in its universal and comprehensive teaching also discusses how production, distribution and consumption should be done. Consumption patterns and production behavior determine the wheels of the economy. The Qur'an as a source of teachings, has teachings on consumption, production and distribution in addition to other economic activities. In the context of production, of course, Muslim producers should not be tempted at all by the habits and behaviors of economists who are committing sins, consuming illicit property, spreading hostility, contradicting the sunnatullah, and causing damage on earth. However, as sophisticated as a tool for calculating the blessings of Allah certainly will not count. In conceptual consumption there are several principles that must be obeyed by Muslim consumers, which include: the principle of halal and good, the principle of absence following the passions, the principle of gratitude. Islamic economic systems offer a system economic distribution which prioritizes the value of freedom of action and action based on religious teachings and the value of justice in ownership which is based on two joints, namely freedom and justice.